On the feasibility of an agricultural revolution: Sri Lanka’s ban of chemical fertilizers in 2021 - Drechsel, Pay; Madhuwanthi, Piumi; Nisansala, Duleesha; Ramamoorthi, Dushiya; Bandara, Thilini (Springer, 2025)
Sri Lanka Government’s ambitious decision to ban synthetic agrochemicals, including chemical fertilizers (and pesticides), in April 2021 made it the first nation in the world to embark on a full-scale transition to – as the Government called it—organic farming, and address concerns about human health and the environment. Previous policies had envisioned a gradual shift, but the sudden ban caught agriculture off guard. Declining foreign exchange reserves to import chemical fertilizers and coinciding peak fertilizer prices appeared to support the timing of the move. However, the ensuing rush for organic fertilizers failed to meet the national demand, resulting in severe losses in rice and export-oriented plantation crops. Facing decreasing yields and food insecurity, the government lifted the ban in November 2021. The events raised critical questions about the necessity and feasibility of such a drastic transition and alternative ways. To explore the general feasibility of transitioning toward organic fertilizers, this study considered the actual and potential availability of biomass to “replace” chemical fertilizers at the national scale as was envisioned by the Government. The analysis focused on the four main national crops and showed that in none of the selected scenarios, Sri Lanka’s actual and potentially available organic fertilizer could supply rice- and plantation-based agrosystems with sufficient nitrogen, not to mention other crops or nutrients. The Government will in every scenario, including one that assumes a stepwise transition, remain compelled to spend significantly on importing organic fertilizer to maintain the required crop yields, which would cost the Government more foreign currency than purchasing chemical fertilizer. Even more costly is purchasing rice to close the national production gap, as Sri Lanka eventually did at the end of its nationwide experiment, which resulted in major food security concerns.